The 3-T Model of Informed Consent for Nonstandard Risk Donors: A Proposal for Transplant Clinical Practice. Issue 11 (22nd October 2021) - Grossi, Alessandra Agnese; Nicoli, Federico; De Feo, Tullia Maria; Cardillo, Massimo; Biffa, Gabriella; Pegoraro, Renzo; Petrini, Carlo; Torelli, Rosanna; Puoti, Francesca; Rossini, Giuseppe; Piccolo, Giuseppe; Vesconi, Sergio; et al.
Abstract : Background: The risk of disease transmission from nonstandard risk donors (NSRDs) is low, and outcomes are similar or better relative to transplants performed with standard criteria donors. However, NSRDs have posed new ethical challenges to the informed consent (IC) process. Based on the shared decision-making model, coinciding with the 3 main timings of the IC process ([1] pretransplant assessments and waiting list registration, [2] time on the waiting list, and [3] time of the organ offer), we put forward a model (3-T Model) to summarize the knowledge on IC for NSRDs and to deliver conceptual and practical support to transplant providers on this emergent issue. Methods: We searched PubMed and analyzed data from our area to provide evidence and ethical arguments to promote standardization of the timing of patient information, degree of patient participation, and disclosure of donor risk factors throughout the 3 stages of the time continuum leading to the potential acceptance of NSRDs. Results: Each of the 3 timings carries special ethical significance and entails well-defined duties for transplant providers relative to patient involvement and information of the benefits and risks associated with NSRDs. Based on our framework, experience, and interpretation of the literature, we put forward a list of recommendations to combine standardization (ie, timing, content, and degree of patient participation) and individualization of IC. Conclusions: The 3-T Model may enable the prevention of physicians' arbitrariness and the promotion of patient-centered care. Future studies will assess the effectiveness of the 3-T Model in transplant clinical practice.